Parental (over-)ambition in competitive youth sport:A multi-theoretical approach - Straub, G. (German Journal of Exercise and Sport Research, 2019)
Parental investments in competitive youth sport are just as indispensable as manifold. Parental ambition against this background can be thought as a particular, inner psychic resource which is brought into the young athletes` career in a similar way just like periodic chauffeur services or financial support. Parental ambition can be defined as an increased achievement motivation by the guardians; it is associated with high expectations and striving for control of the children. In this article, the attempt is to make plausible both parental ambition and parental over-ambition by using various theoretical models. Regarding the emergence of an innocuous or possibly functional type of ambition and the pathological form of over-ambition, an inadequate personality development in over-ambitious parents is believed to be the distinctive feature. In order to understand better the genesis and consequences of excessive parental ambition, thoughts are presented which are psychoanalytic in nature. In this context, the role-theory by the German family therapist Horst-Eberhard Richter and Heinz Kohut`s self-psychology are fundamental for providing explanatory performance. Moreover, the expectancy-value model by the pedagogical psychologist Jacquelynne S. Eccles has been proven useful in order to account for interindividual and interfamilial variations in parental ambition on an everyday basis. Finally, implications for scientific research and sport practice are presented. Zusammenfassung: Das elterliche Engagement im Nachwuchsleistungssport ist so unentbehrlich wie vielfältig. Elterlicher Ehrgeiz kann vor diesem Hintergrund als besondere innerpsychische Ressource betrachtet werden, die in den Werdegang der jungen Sportler auf ähnliche Weise einfließt wie regelmäßige Chauffeurdienste oder finanzielle Unterstützung. Elterlicher Ehrgeiz lässt sich als eine erhöhte Leistungsmotivation durch die Erziehungsberechtigten definieren; assoziiert ist er mit hohen Erwartungen und dem Bestreben, die Kinder zu kontrollieren. Im vorliegenden Beitrag wird versucht, mithilfe verschiedener theoretischer Modelle sowohl elterlichen Ehrgeiz als auch Überehrgeiz plausibel zu machen. Bezüglich des Auftretens eines harmlosen oder vielleicht funktionellen Ehrgeiztyps und der pathologischen Form des Überehrgeizes nimmt man an, dass eine unzureichende Persönlichkeitsentwicklung bei überehrgeizigen Eltern den Unterschied ausmacht. Um die Entstehung sowie die Folgen eines übermäßigen elterlichen Ehrgeizes besser verstehen zu können, werden psychoanalytische Betrachtungen angestellt. In diesem Zusammenhang sind die Rollentheorie des deutschen Familientherapeuten Horst-Eberhard Richter und die Selbstpsychologie von Heinz Kohut grundlegend für das Erklärungspotenzial. Darüber hinaus hat sich das Erwartungs-mal-Wert-Modell der pädagogischen Psychologin Jacquelynne S. Eccles dahingehend als nützlich erwiesen, interindividuelle und interfamiliäre Unterschiede hinsichtlich elterlichen Ehrgeizes im alltäglichen Miteinander einzubeziehen. Abschließend wird die Relevanz für die wissenschaftliche Forschung und Sportpraxis dargelegt.